Shaft Voltage Suppression of Double-fed Generator for High Power Wind Turbine - CAO Guorong; ZHAO Yanfeng; TANG Jianping; WANG Baogui; YUAN Ying; WANG Ying (Kongzhi Yu Xinxi Jishu)
The mechanism and adverse effects of shaft voltage in double-fed generator generated by inverter is analyzed. As shaft voltage is part of common-mode voltage, a new LCL-filter of converter for suppression of common-mode voltage is proposed through discussion of the characteristics and transmission path of common-mode voltage. Experimental results verify the validity of the new filter.